MODL-31. Novel in vivo models of post-radiation recurrent pediatric high-grade glioma show increased susceptibility to MAPK inhibition. (3rd June 2022) - Knox, Aaron; DeSisto, John; Nelson-Taylor, Sarah; Coleman, Philip; Van Court, Benjamin; Donson, Andrew; Karam, Sana; Green, Adam
Abstract: BACKGROUND: Pediatric high-grade glioma (pHGG) is the most common cause of childhood cancer mortality, with median survival of less than one year. The standard of care for pHGG includes radiation therapy (RT), but almost all patients who respond initially relapse with aggressive, radiation-resistant disease. Matched primary/recurrent models and effective therapies for recurrent pHGG have not been adequately developed. METHODS: Orthotopic patient derived xenograft (PDX) models of radiation-resistant pHGG were developed by implanting BT245 (H3K27M) and HSJD-GBM-001 (GBM1, H3-wt) cells into mice. Resultant tumors were irradiated at 8Gy (4Gy x 2d) and allowed to regrow. Recurrent, radiation-resistant tumors (BT245MR and GBM1MR) and initial tumors (BT245M and GBM1M) were collected for bulk RNA-Seq analysis and ex vivo cell culture. Dose-response experiments were conducted in explant cells to identify drugs with increased effectiveness against recurrent (MR) cell lines versus wild-type cell lines. RESULTS: In both BT245 and GBM1 explant cells, geneset enrichment analysis (GSEA) showed upregulated mesenchymal (BT245MR: NES=3.4, FDR=0; GBM1MR: NES=2.4, FDR<0.002) and hypoxia-related (BT245MR: NES=3.6, FDR=0; GBM1MR: NES=3.4, FDR=0) pathways. GBM1MR tumors also showed enrichment in MAPK signaling (NES=4.7, FDR=0). RNA processing (NES=-6.5, FDR=0) and translation (NES=-5.8, FDR=0) pathways were depleted in BT245MR cells, and DNA repair pathways (NES=-5.8, FDR=0) were depleted in GBM1MR cells. The MAPK inhibitor trametinib demonstrated increased effectiveness in BT245MR and GBM1MR cell lines versus wild-type controls (BT245 IC50 158.7nM (wt) vs. 56.0 (MR), p<0.05; GBM1 IC50 150.7 (wt) vs. 53.4 (MR), p<0.05). BT245MR and GBM1MR cells reliably form PDX tumors after injection into mice. CONCLUSION: BT245MR and GBM1MR represent novel in vivo models of radiation-resistant pHGG, with gene expression alterations consistent with an irradiated phenotype. GSEA and in vitro dose-response data suggest MAPK inhibition may be effective in radiation-resistant pHGG. We are currently conducting in vivo experiments to validate increased trametinib sensitivity in these models.